(untitled) (GIST – Education and Learning Research Journal, 2021)
There has been a continuing interest in defining what comprises English teachers’ knowledge with the purpose of defining the boundaries of the English Teaching field and developing it as a respected discipline in education (Richards, 1990). The objective of this paper, shaped by the tenets of the Decolonial Turn, is to share some of the results of studying teachers’ knowledge with a view of knowledge described by Anzaldúa (2000) as “an overarching theory of consciousness… that tries to encompass all the dimensions of life, both inner –mental, emotional, instinctive, imaginal, spiritual, bodily realms—and outer—social, political, lived experiences.” (p. 177). Data were gathered by means of testimonial narratives, and their analysis followed some guidelines of Benmayor’s (2012) framework of testimonial narratives writing and communal analysis. The study is also inspired by and grounded on the Epistemologies of the South (Sousa Santos, 2004, 2006, 2016, 2018) to think of knowledge beyond the cognitive experiences of teachers. Some of the results show that teachers’ knowledge is something experienced by them not only in their cognition but also in their emotions and body. Not only do teachers rely on content, pedagogical or methodological knowledge, but also on emotion, as evidenced in a sample of teachers’ testimonial narratives.